A Histometric Analysis of Chronically Rejected Human Liver Allografts: Insights into the Mechanisms of Bile Duct Loss: Direct Immunologic and Ischemic Factors - Oguma, Shiro (1989)
Conspicuous pathologic features of chronic liver allograft rejection include bile duct loss and chronic obliterative arteriopathy. A quantitative histometric analysis was performed to document the extent of bile duct loss, the size of the “vanished” ducts and the extent of chronic obliterative arteriopathy and to determine whether there was any relationship between chronic obliterative arteriopathy and bile duct loss. All failed liver allograft specimens with chronic rejection were reviewed and categorized according to the degree of chronic obliterative arteriopathy, assessed by the degree of luminal narrowing of hilar hepatic artery branches. Histometric analysis of the grafts revealed: (i) there was a loss of small portal arterioles (<35 μm); (ii) bile ducts which should accompany arteries <35, 35 to 54 or 55 to 74 μm in diameter were missing, with the greatest decrease occurring among the smallest ducts; (iii) bile duct loss was seen in the absence of significant large vessel chronic obliterative arteriopathy, and (iv) the severity of arteriole and bile duct loss, as well as the size of the vanished ducts, was directly proportional to the degree of chronic obliterative arteriopathy. Furthermore, the size of the “vanished” bile ducts in liver allografts appeared to differ from the size of ducts destroyed in primary biliary cirrhosis. These studies offer indirect, but suggestive proof that two mechanisms are operative in the bile duct loss seen in chronic rejection: direct lymphocytotoxicity and ischemic damage.